Pengembangan Koperasi ASN di Kabupaten Kutai Kartanegara: Analisis potensi, permasalahan, dan arah kebijakan - Panasiah, Santi Eka; Aini, Aini (STAI Auliaurrasyidin Tembilahan, 2025)
The welfare of State Civil Apparatus (ASN) significantly influences their performance, making the formation of cooperatives a vital economic empowerment strategy. This study aims to analyze the potential, challenges, and strategies for developing effective and sustainable ASN cooperatives. The research method used a qualitative descriptive survey, through primary data collection by distributing questionnaires to 387 ASN out of a total of 12,022 using the Slovin formula with a sampling error of 5%. The results showed that 88% of respondents fully supported the diversification of cooperative services. The most popular service was savings and loans (35.7%). However, there are three crucial challenges: (1) low awareness of the role of cooperatives; (2) Weak governance and management (including financial transparency); and (3) lack of inspirational figures. ASN cooperatives in Kutai Kartanegara have high potential for development, especially the savings and loans model. For sustainability, a professional and participatory strategy is needed, including the implementation of web-based technology for management transparency and strengthening member education. It is recommended that a Regent's regulation be issued to systematically regulate the management and supervision of ASN, in order to improve welfare and strengthen the local economy.